The In Silico Insights of α-Adrenergic Receptors Over the Last Decade: Methodological Approaches and Structural Features of the 3D Models - Carrieri, Antonio; Fano, Alessandra (Current Topics in Medicinal Chemistry, 2007)
Homology modeling has been widely used in the latest years in order to overcome the lackness of adequate structural information. This technique has also been successfully applied in the very difficult but challenging field of Gprotein coupled receptors where the need of three-dimensional insight is significantly more essential. Here we will review the latest advancements in this topic taking as case studies α-adrenergic receptors theoretical models and their structural features.
Keywords: docking